Pengaruh Self-Regulation dan Student Satisfaction terhadap Kinerja Akademik pada Mahasiswa Akuntansi di Surabaya - Gunawan Iriyanto; Fernando Ruslim; Sany Sany (Business Accounting Review, 2021)
This paper examines the effect of self-regulation and student satisfaction levels affects the academic performance of accounting students in Surabaya while participating in online learning during the Covid-19 pandemic. The sample data in this study were 341 accounting student respondents in the city of Surabaya which were obtained through the distribution of online surveys. Data analysis and hypothesis testing in this study using PLS (Partial Least Square) software as part of the Structural Equation Modeling technique. The results in this study indicate that accounting students from several universities in the city of Surabaya have self-regulation and have good student satisfaction in participating in the online learning process which has a significant influence on student academic performance. Good independent learning carried out by students in this study is in accordance with social cognitive theory which refers to cognitive structures that provide references to how one behaves and how a person feels, evaluates and regulates their own behavior well and also depends on the social environment that surrounds them. With good learning and the satisfaction felt by students during good learning has a positive influence on their academic performance.